What factors promote student resilience on a level 1 distance learning module?. (2nd January 2018) - Simons, Joan; Beaumont, Kythe; Holland, Lesley
Abstract: Resilience is understood to be the ability to adapt positively in the face of adversity. In relation to new students on a distance learning module, this can mean how they adapt and make sense of the demands of their chosen study to enable them to persist in their studies. This article reports a small-scale study involving semi-structured telephone interviews with students on a level 1 distance learning module at the UK Open University. Students identified the challenges they experienced such as carving out time to study alongside other commitments, as well as developing their academic writing. Students also identified factors that enabled them to adapt to these challenges and be successful in continuing to study. Students rated highly the support they received from tutors in the form of tailored, detailed feedback on their assignments. Other factors that enabled students to persist in their studies were time management, self-belief and motivation.